Enhanced microalgae biomass and lipid output for increased biodiesel productivity. (January 2021) - Morais, Keli C.C.; Conceição, Daniele; Vargas, José V.C.; Mitchell, David A.; Mariano, André B.; Ordonez, Juan C.; Galli-Terasawa, Lygia Vitoria; Kava, Vanessa M.
Abstract: This paper investigated the cumulative impact of salinity, carbon source (glycerol and glucose) and photoperiod on the cultivation of the microalga Phaeodactylum tricornutum in mixotrophic growth in pure air supplied photobioreactors aiming at biomass output and lipid content enhancement for increased biodiesel productivity. For that, Phaeodactylum tricornutum was grown for 18 and 20 days in modified F2 medium which was supplied in the beginning of the culture, and with daily addition of glycerol (0.1 M) or glucose (0.05 M); salinity at 15 and 30‰, with the luminosity of 165 μmols photons m −2 s −2 for 24 h day −1 or partial 12 h day −1 . Biomass production was registered, total lipids quantified with the Bligh and Dyer methodology, and the lipids' drops observed with Nile Red staining. Regarding salinity, a value of 15‰ led to the highest microalgae growth. Glycerol 0.1 M was the carbon source which provided the best assimilation by the microalgae, reaching up to 1.3 g L −1 of biomass. The 24 h-illumination photoperiod with glycerol in mixotrophic cultivation led to 338.97 mg L −1 of lipids, which was roughly 80% higher than the lipid content obtained with autotrophic growth. In conclusion, the most effective conditions were glycerol 0.1 M (carbon source), 15‰ salinity, and 24 h-illumination. Graphical abstract: Image 1 Highlights: Salinity, carbon source and photoperiod effect on microalgae growth. No CO2 injection on microalgae mixotrophic cultivation outcome. Lipids identification with Nile Red staining. Glycerol and glucose comparative analysis on lipid production. Glycerol addition produced 80% more lipid content than autotrophic growth.